Cell-Derived Matrix: Production, Decellularization, and Application of Wound Repair - Yidan Xu; Yao Yao; Jianhua Gao (Stem Cells International)
Chronic nonhealing wounds significantly reduce patients’ quality of life and are a major burden on healthcare systems. Over the past few decades, tissue engineering materials have emerged as a viable option for wound healing, with cell-derived extracellular matrix (CDM) showing remarkable results. The CDM’s compatibility and resemblance to the natural tissue microenvironment confer distinct advantages to tissue-engineered scaffolds in wound repair. This review summarizes the current processes for CDM preparation, various cell decellularization protocols, and common characterization methods. Furthermore, it discusses the applications of CDM in wound healing, including skin defect and wound repair, angiogenesis, and engineered vessels, and offers perspectives on future developments.